Neuroinflammation and Sleep Dysfunction in Epilepsy: The Role of High Sensitivity C-Reactive Protein - Akmal Irsyadi Iswan; Restu Susanti; Lydia Susanti; Syarif Indra; Fanny Adhy Putri; Reno Bestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Emerging evidence suggests a bidirectional relationship between systemic inflammation and both epilepsy and sleep dysfunction. High-sensitivity C-reactive protein (Hs-CRP), a sensitive marker of low-grade systemic inflammation, is elevated in response to pro-inflammatory cytokines. However, the specific link between Hs-CRP levels and subjective sleep quality within the epilepsy population required further investigation. This study aimed to investigate the relationship between serum Hs-CRP levels and sleep quality in patients diagnosed with epilepsy. Methods: A cross-sectional study was conducted involving 40 patients diagnosed with epilepsy attending the neurology clinic at Dr. M. Djamil General Hospital, Padang, Indonesia, between January and February 2025. Patients aged over 17 years diagnosed by a neurologist were included. Serum Hs-CRP levels were quantified using an enzyme-linked immunosorbent assay (ELISA). Sleep quality over the preceding month was assessed using the validated Indonesian version of the Pittsburgh Sleep Quality Index (PSQI). Mann-Whitney U test was employed to analyze the difference in median Hs-CRP levels between patients with good and poor sleep quality. Relationships between baseline characteristics and sleep quality were assessed using Chi-square/Fisher's exact tests for categorical variables and the Mann-Whitney U test for continuous variables. Results: Forty epilepsy patients (median age 25.5 years, range 17-50; 52.5% female) were enrolled. The median duration of epilepsy was 10 years (range 1-35). A majority of patients exhibited uncontrolled seizures (75%) and were receiving AED polytherapy (60%). Based on PSQI scores, 24 patients (60%) were classified as poor sleepers, while 16 (40%) were good sleepers. A significant difference was observed in median serum Hs-CRP levels between the two groups: patients with good sleep quality had significantly lower median Hs-CRP levels compared to those with poor sleep quality (1,271.50 ng/ml [range 58–5,837] vs. 2,771.50 ng/ml [range 509–27,187], p=0.027). Poor sleep quality was significantly associated with younger age (median 23 vs. 36 years, p=0.039) and AED polytherapy (75% vs. 25%, p=0.018). Conclusion: This study demonstrated a significant association between elevated serum Hs-CRP levels and poor subjective sleep quality in patients with epilepsy. Epilepsy patients experiencing poor sleep exhibited significantly higher levels of this inflammatory biomarker. These findings underscore the potential role of systemic inflammation in the complex interplay between epilepsy and sleep disturbances, suggesting Hs-CRP could serve as a potential biomarker linking these conditions.